Pengaruh Emotional Bias dan Mental Accounting Terhadap Keputusan Pembelian Gacha Game Mobile Legends (Studi Kasus Mahasiswa Universitas Kiai Haji Achmad Siddiq Jember) - M. Mirza Pratama; Ainun Nisa Nurhidayat Hakim (CV. ITTC INDONESIA, 2025)
The advancement of digital technology has driven changes in consumer behavior, particularly through microtransactions in online games. Mobile Legends: Bang Bang, one of the most popular online games, offers in-game purchases through a gacha system a luck-based lottery mechanism that often leads to irrational purchasing decisions. This study aims to analyze the influence of Emotional Bias and Mental Accounting on gacha item purchasing decisions among students at the State Islamic University of Kiai Haji Achmad Siddiq Jember. A quantitative approach was used with a survey method, distributing questionnaires to 104 respondents selected through purposive sampling. The data were analyzed using multiple linear regression with the assistance of SPSS software. The results show that Emotional Bias and Mental Accounting simultaneously affect purchasing decisions. Partially, each independent variable also has a significant effect on the purchasing decision. These findings indicate that psychological factors play a crucial role in students’ digital economic behavior and highlight the need for better financial literacy to prevent impulsive and speculative consumption decisions.